2016
DOI: 10.1116/1.4954642
|View full text |Cite
|
Sign up to set email alerts
|

Thickness characterization of atomically thin WSe2 on epitaxial graphene by low-energy electron reflectivity oscillations

Abstract: In this work, low-energy electron microscopy is employed to probe structural as well as electronic information in few-layer WSe 2 on epitaxial graphene on SiC. The emergence of unoccupied states in the WSe 2 -graphene heterostructures are studied using spectroscopic low-energy electron reflectivity. Reflectivity minima corresponding to specific WSe 2 states that are localized between the monolayers of each vertical heterostructure are shown to reveal the number of layers for each point on the surface. A theory… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…Fu et al, observed that a single orientation was favored in MBE when lower metal flux was used (91). Similar single oriented domains have been observed for WS2 (95) and WSe2 (Figure 6e) (56). Preference of a single orientation was explained based on metal atoms reacting with the BN defects and acting as nucleation or anchoring sites.…”
Section: Van Der Waals Substratessupporting
confidence: 55%
“…Fu et al, observed that a single orientation was favored in MBE when lower metal flux was used (91). Similar single oriented domains have been observed for WS2 (95) and WSe2 (Figure 6e) (56). Preference of a single orientation was explained based on metal atoms reacting with the BN defects and acting as nucleation or anchoring sites.…”
Section: Van Der Waals Substratessupporting
confidence: 55%
“…In addition to LEEM imaging, we obtain spectroscopic information of the sample under study by measuring the intensity of elastically reflected electrons as a function of the incidence electron kinetic energy, a technique called low-energy electron reflectivity (LEER). 56,59,60 In thin-film materials like graphene and transition metal dichalcogenides, the layer confinement of electrons leads to quantum-well states with energy spacing depending on the film thickness. 56,60 In the LEER experiment, incident electrons can couple resonantly to unoccupied quantum-well states, i.e., conduction bands with the wave vector perpendicular to the film, and experience a decreased reflection probability.…”
Section: F Low-energy Electron Microscopy (Leem) and Reflection (Leer)mentioning
confidence: 99%
“…56,59,60 In thin-film materials like graphene and transition metal dichalcogenides, the layer confinement of electrons leads to quantum-well states with energy spacing depending on the film thickness. 56,60 In the LEER experiment, incident electrons can couple resonantly to unoccupied quantum-well states, i.e., conduction bands with the wave vector perpendicular to the film, and experience a decreased reflection probability. These distinct reflection minima result in a fingerprint for a given material and integer number of monolayers, which we can examine with high resolution in our setup.…”
Section: F Low-energy Electron Microscopy (Leem) and Reflection (Leer)mentioning
confidence: 99%
See 1 more Smart Citation
“…We replace the delta function of E L − E R with a version in terms of k, 5) where the zero of f (k R , k L ) is found using Eq. (B.4) to be region I: 6) with k = eV / v F . From this, it follows that |f (k 0 )| = v F .…”
Section: B1 Monolayer Graphenementioning
confidence: 99%